THE EFFECT OF COOPERATIVE LEARNING MODELS ON INCREASING LEARNING RESULTS AND STUDENT ACTIVITIES IN MATHEMATIC LESSONS - Nur Alim Noor; Imam Munandar (JME (Journal of Mathematics Education), 2019)
This study aims to determine the effect of cooperative learning models on improving learning outcomes and student learning activities in mathematics. This type of research is quantitative. The research design used was quasi-experimental by taking three sample classes. Two as the experimental class that received the treatment of cooperative learning model type Team Assisted Individualization (TAI) and Think Pair Share (TPS) type. One control class received conventional method treatment. The sample was taken from class X Kosgoro Vocational School Karawang Regency with a sample size of 90 students. Data was taken by post test by using objective test instruments with 25 multiple choice items for learning mathematics matrix material and for student learning activity data using a questionnaire consisting of 30 items in the Likert point 5. The results of data analysis showed that TAI learning was better than Conventional, can be proved statistically (LSD table) that the mathematics learning outcomes are Sig = 0.002 and for learning activities Sig = 0.000, both are smaller than α = 0.05. This proves that TAI learning is better than conventional seen from the results of learning and student learning activities. Learning TPS is better than Conventional, can be proven statistically (LSD table) that for mathematics learning outcomes obtained Sig = 0.684 greater than α = 0.05 and for learning activities obtained Sig = 0.002 smaller than α = 0.05. This proves that TPS learning is better than Conventional seen from student learning activities even for student learning outcomes there is no difference. Based on the data analysis, it can be concluded that the application of cooperative learning models can influence the increase in mathematics learning outcomes and student learning activities.